Careers in sports and fitness - Schmidt, Debra (Exploring careers (ReferencePoint Press), 2016)
Comments from people in the industry, current statistics and forecasts, and realistic descriptions provide a useful look at sports and fitness jobs ranging from athletic trainers to recreation therapists, to sports medicine physicians.